Characterization of Children with Autism Spectrum Disorder's Interactions with a Service Dog During Their First Encounter. (2nd November 2022) - Dollion, Nicolas; Herbin, Alexandre; Champagne, Noël; Plusquellec, Pierrich; Grandgeorge, Marine
ABSTRACT : Reports reveal various benefits of animals – especially dogs – for children with autism spectrum disorders (ASD). However, not all children with ASD display the same interest in animals. Dogs are the most common pets in households that have children with ASD and they are the only species to be used as service animals for these children. They are also the most commonly used species in animal-assisted interventions. Despite the key role that both the interest and behaviors displayed toward dogs might play in their benefits to children with ASD, no studies have yet investigated this aspect using direct observation. Applying an ethological approach, this study aimed to explore and characterize how children with ASD interact with a service dog during a first encounter. Video recordings of 20 children with ASD in free interactions during their first encounter with a service dog were analyzed. Our results indicate that children with ASD are attracted to service dogs, but we found important individual differences. We distinguished two main behavioral interaction profiles (one more distal with the service dog and the other more proximal and attracted to the service dog). Our results show that the children with ASD's interaction strategies vary according to their age and ASD severity: younger children made fewer physical contacts with the service dog, gazed less at it, and displayed less care behaviors, while children with severer ASD seemed to rely on a smaller behavioral repertoire when interacting with a service dog. This study is the first to characterize how children with ASD interact with a service dog during their first encounter. These findings open onto future research concerning the importance of a child with ASD's attraction to and behavior in the presence of an animal, as well as of the impacts of a child's characteristics (i.e., age, ASD severity, and sensory processing disorder) to be able to improve programs for animal-assisted interventions.